THE NOUN GROUP AND ITS GRAMMATICAL CATEGORIES - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Language is a social phenomenon and every language has its own grammar. For many centuries such famous scholars as B. Illyish, M. Y. Blokh, O. Jesperson and many others had investigated the problem of parts of speech, that causes great controversies both in general linguistic theory and in the analysis of separate languages. And the main question that had interested them was noun as a part of speech